Marine Biodiversity in Inútil Bay (Tierra del Fuego): Patterns of Zooplanktonic and Benthic Assemblages - Rodriguez Stepke, Benjamin; Montiel San Martin, Americo Manuel; Poblete, Jonathan; Landaeta, Mauricio; Perez, Daniel; Perez Schultheiss, Jorge; Skamiotis, Kharla; Garrido, Ignacio; Orrego, Fernanda S.; Hune, Mathias (My University, 2025)
Southern Patagonian ecosystems are characterized by high environmental heterogeneity. Within this context, Inútil Bay exhibits a complex geomorphology and only fragmentary information on its biodiversity, despite a long history of resource exploitation and increasing human pressures. The objective of this study was to establish a baseline of biodiversity focusing on three key trophic components: zooplankton, megabenthos, and macrobenthos. Samples were collected using both traditional and non-invasive methods, including a bongo net, ROV, and Van Veen grab. A total of 239 taxa were identified, comprising 32 zooplankton species, 61 megabenthic taxa, and 146 macrobenthic taxa. Alpha diversity indices revealed a spatial gradient, with higher mixed-level taxonomic richness near the Whiteside Channel. In contrast to patterns observed in zooplankton and megabenthos, the macrofauna showed significant differences between assemblages at stations located inside and outside the bay. Moreover, a low representation of meroplankton was recorded compared to the high abundance of adult benthic invertebrates. Overall, these results provide a biodiversity baseline, underscore the ecological vulnerability of Inútil Bay, and support its recognition as a priority area for conservation.
Keywords: community structure; magellan province; benthic macrofauna; zooplankton